Precision meets repurposing: Innovative approaches in human papillomavirus and Epstein-Barr virus-driven cancer therapy - Queenie Fernandes (14557388) (2024)
Viral malignancies represent a distinct entity among cancers. Oncoviruses like the Human Papilloma Virus (HPV) and the Epstein Barr Virus (EBV) are highly potent inducers of oncogenic transformation leading to tumor development. HPV and EBV are known to be increasingly involved in the pathogenesis of various classes of cancers like cervical, head and neck, colorectal, breast, oral and anogenitial. Therapeutic vaccines directed at such oncoviruses, often fail to unleash the desired immune response against the tumor. This is largely due to the immunosuppressive microenvironment of the virus-induced tumors. Consequently, metronomic chemotherapies administered in conjunction with therapeutic viral vaccines have considerably enhanced the antitumor activity of these vaccines. Moreover, given the unique attributes of HPV and EBV-associated cancers, therapeutic agents directly targeting the oncoproteins of these viruses are still obscure. In this light, an increasing number of reports have evidenced the repurposing of drugs for therapeutic benefits in such cancers. This work delineates the significance and implications of metronomic chemotherapy and drug repurposing in HPV and EBV-associated cancers. Other Information Published in: Cancer Letters License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.canlet.2024.217318